To study TIG arc and welding characteristic / Amran Abd Rahman and Mohd Fisol Fadhil - Abd Rahman, Amran; Fadhil, Mohd Fisol (1995)
The objective of our project is to analyse the parameters of TIG arc welding. In welding there are certain particular characteristics which are dictated by the nature of the application. All parameters like type of current used, current value, voltage, electrode shape and type welding speed will be recorded and they will be used to analyse the behaviour of the arc in welding.